Cartoon guide to the Environment - Gonick, Larry; Outwater, Alice (New York Harper Collins, 2014)
Do you think that the Ozone Hole is a grunge rock club? Or that the Food Web is an on-line restaurant guide? Or that the Green Revolution happened in Greenland? Then you need The Cartoon Guide to the Environment to put you on the road to environmental literacy. The Cartoon Guide to the Environment covers the main topics of environmental science: chemical cycles, life communities, food webs, agriculture, human population growth, sources of energy and raw materials, waste disposal and recycling, cities, pollution, deforestation, ozone depletion, and global warming$1 (Band puts them in the context of ecology, with discussions of population dynamics, thermodynamics, and the behavior of complex systems.s
Keywords: Enviromental Science; Caricatures and cartoons; Environmental Education; Caricatures and cartoon